Rethinking Manure Application: Increase in Multidrug-Resistant Enterococcus spp. in Agricultural Soil Following Chicken Litter Application - Dorcas Oladayo Fatoba; Akebe Luther King Abia; Daniel G. Amoako; Sabiha Y. Essack (Microorganisms, 2021)
The current study investigated the impact of chicken litter application on the abundance of multidrug-resistant Enterococcus spp. in agricultural soil. Soil samples were collected from five different strategic places on a sugarcane farm before and after manure application for four months. Chicken litter samples were also collected. Enterococci were enumerated using the Enterolert®/Quanti-Tray 2000® system and confirm and differentiated into species using real-time PCR. The antibiotic susceptibility profile of the isolates was determined using the disk diffusion method following the European Committee on Antimicrobial Susceptibility Testing (EUCAST) guidelines. The overall mean bacterial count was significantly higher (p < 0.05) in manure-amended soil (3.87 × 107 MPN/g) than unamended soil (2.89 × 107 MPN/g). Eight hundred and thirty-five enterococci (680 from soil and 155 from litter) were isolated, with E. casseliflavus being the most prevalent species (469; 56.2%) and E. gallinarum being the least (16; 1.2%). Approximately 56% of all the isolates were resistant to at least one antibiotic tested, with the highest resistance observed against tetracycline (33%) and the lowest against chloramphenicol (0.1%); 17% of E. faecium were resistant to quinupristin-dalfopristin. Additionally, 27.9% (130/466) of the isolates were multidrug-resistant, with litter-amended soil harbouring more multidrug-resistant (MDR) isolates (67.7%; 88/130) than unamended soil (10.0%; 13/130). All isolates were susceptible to tigecycline, linezolid and gentamicin. About 7% of the isolates had a multiple antimicrobial resistance index > 0.2, indicative of high antibiotic exposure. Although organic fertilizers are regarded as eco-friendly compared to chemical fertilizers for improving soil fertility, the application of untreated animal manure could promote the accumulation of antibiotics and their residues and antibiotic-resistant bacteria in the soil, creating an environmental reservoir of antimicrobial resistance, with potential human and environmental health risks.